Rurality and Capital: Educational Expectations and Attainments of Rural, Urban/Rural and Metropolitan youth - Andres, Lesley; Looker, E. Dianne (Canadian Journal of Higher Education, 2001)
This paper uses data from two longitudinal surveys of Canadian youth to examine the effects of rural versus urban/rural and metropolitan residence on young people’s educational expectations and attainments. The surveys are based in British Columbia (B.C.) and Nova Scotia (N.S.), two provinces that have very different systems of postsecondary education. B.C. has an articulated system with formal structures which allow students to take the first two years of university study at a community college before transferring to a university. N.S. has no such formal transfer system. Its community college system is not well developed but it has a large number of universities, some of which are in rural areas. The findings show that, in both provinces, students in rural areas have lower expectations and attainments compared to other students, even when parental background, gender and academic stream are controlled. A comparison across provinces shows that rural youth in B.C. are more likely than their N.S. counterparts to pursue postsecondary education, but rural N.S. youth are more likely to have successfully completed a degree program four to five years after high school. Implications of these findings for future research as well as for policy changes in the two provinces are discussed.